2020
DOI: 10.1007/s10072-019-04204-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of carotid stenosis ultrasound scale in the prediction of ischemic stroke

Abstract: Introduction To improve the accuracy of ultrasound techniques for the assessment of carotid stenosis, we designed a novel carotid artery stenosis ultrasound scale (CASUS), and evaluated its accuracy, reliability, and its value in predicting the occurrence of cardiovascular and cerebrovascular diseases in a prospective study. Methods A total of 750 patients with first-time ischemic stroke and hospitalized within 24 h were enrolled in the study. Using color Doppler ultrasound (CDUS), the degree of stenosis and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 22 publications
2
10
0
Order By: Relevance
“…the previous studies (14,24). Many studies demonstrated that the CBF decreased with the increase of the carotid stenosis degree (14,24).…”
Section: Discussionmentioning
confidence: 83%
“…the previous studies (14,24). Many studies demonstrated that the CBF decreased with the increase of the carotid stenosis degree (14,24).…”
Section: Discussionmentioning
confidence: 83%
“…In addition, Doppler ultrasound is currently the preferred noninvasive CAS detection method, which is simple, safe, and low-cost. However, it cannot detect intracranial CAS lesions, and the results are easily affected by the skill level of the operator [ 29 ]. Therefore, dynamic circulating blood and serum biomarkers have attracted extensive attention [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large number of studies have demonstrated that carotid stenosis plays an important role in the reduction in the preoperative CBF. 10,16,17 Jongen et al 17 reported that, in patients with unilateral symptomatic carotid stenosis of ≥50%, rCBF declined with carotid stenosis increased. A clinical study including 750 patients with ischemic stroke also reported the decreased blood flow accompanied by the increased degree of carotid stenosis 16 …”
Section: Discussionmentioning
confidence: 99%